2022
DOI: 10.48550/arxiv.2201.08370
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

TESS Revisits WASP-12: Updated Orbital Decay Rate and Constraints on Atmospheric Variability

Ian Wong,
Avi Shporer,
Shreyas Vissapragada
et al.

Abstract: After observing WASP-12 in the second year of the primary mission, the Transiting Exoplanet Survey Satellite (TESS) revisited the system in late 2021 during its extended mission. In this paper, we incorporate the new TESS photometry into a reanalysis of the transits, secondary eclipses, and phase curve. We also present a new K s -band occultation observation of WASP-12b obtained with the Palomar/WIRC instrument. The latest TESS photometry span three consecutive months, quadrupling the total length of the TESS … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 64 publications
(116 reference statements)
0
2
1
Order By: Relevance
“…From our result of Q , the estimated spiral in-fall timescale is around 5 × 10 7 yr, which is longer than originally expected. For comparison, WASP-12b, the only planet with confirmed tidal decay so far has a corresponding Q = (1.50 ± 0.11) × 10 5 (Wong et al 2022), which is two orders of magnitude lower than the minimum value we found for WASP-18. WASP-12 is also an F-type star, with an effective temperature of 6150 K, with a mass similar to WASP-18.…”
Section: Resultscontrasting
confidence: 60%
See 2 more Smart Citations
“…From our result of Q , the estimated spiral in-fall timescale is around 5 × 10 7 yr, which is longer than originally expected. For comparison, WASP-12b, the only planet with confirmed tidal decay so far has a corresponding Q = (1.50 ± 0.11) × 10 5 (Wong et al 2022), which is two orders of magnitude lower than the minimum value we found for WASP-18. WASP-12 is also an F-type star, with an effective temperature of 6150 K, with a mass similar to WASP-18.…”
Section: Resultscontrasting
confidence: 60%
“…Its orbit is shrinking at a rate of 29.81 ± 0.94 ms yr −1 , leading to a decay timescale of 3.16 ± 0.10 Myr. The tidal quality factor of Q = (1.50 ± 0.11) × 10 5 is thought to be on the lower side of the predicted values (Wong et al 2022).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation